Social media as an informal educational tool for raising awareness of sexual harassment in urban communities - Emmanuel Olugbenga Sijuade (Asian Journal Collaboration of Social Environmental and Education, 2026)
Background: The study examined the Perception of Social Media on Awareness of Sexual Harassment in Nigeria. The rationale behind the study were various type of social media used by residents of Festac Town, Lagos, identify to what extent respondents who use social media understand what sexual harassment means, determine how social media have helped in creating awareness on sexual harassment amongst residence of Festac town, Lagos and to determine the moral standards that social media platforms must adhere to when raising awareness of sexual harassment. The theories employed for the study are Perception theory and Developmental Media theory. Methods: The methodology for the study was survey and the research instrument used was the self-administered questionnaire to collect relevant information from the population, however a total of three hundred and seventy copies of the questionnaire were administered and sample random sampling was used to select the respondents. The data gathered were analyzed using Statistical Package for Social Sciences (SPSS) in form of tables, percentages and frequency count. Findings: The findings of the study disclosed that most respondents agreed that social media have helped in creating awareness among residents of Festac Town, Lagos and social media helps in letting messages out to the larger community which will hopefully inspire change, social media helps in calling the attention of government agencies to cases of sexual harassment. Conclusion: The study concluded that a large number of respondents think that social media have a positive impact on the Awareness of Sexual Harassment in Nigeria, the study also revealed that the Twitter and Instagram are the major social media platform that helps in raising awareness for sexual harassment. Novelty/Originality of this article: The study recommends that information on social media should be regulated by some regulatory bodies and caution is needed before such information is broadcasted to the people in order not to stiff up hatred and stereotype judgment on some people or societies.